Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure! Let's determine the composite function [tex]\( g \cdot f \)[/tex], which is represented as [tex]\( g(f(x)) \)[/tex].
Given:
[tex]\[ f(x) = x^2 - 3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
First, we need to find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x^2 - 3 \][/tex]
Next, we apply the function [tex]\( g \)[/tex] to the result of [tex]\( f(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x^2 - 3) \][/tex]
Since the function [tex]\( g \)[/tex] is defined as [tex]\( g(x) = x + 1 \)[/tex], we substitute [tex]\( x^2 - 3 \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(x^2 - 3) = (x^2 - 3) + 1 \][/tex]
Simplifying the expression, we get:
[tex]\[ g(x^2 - 3) = x^2 - 3 + 1 \][/tex]
[tex]\[ g(x^2 - 3) = x^2 - 2 \][/tex]
Hence, the composite function [tex]\( g \cdot f \)[/tex] is:
[tex]\[ g(f(x)) = x^2 - 2 \][/tex]
Let's verify this composite function with an example input, [tex]\( x = 2 \)[/tex]:
First, calculate [tex]\( f(2) \)[/tex]:
[tex]\[ f(2) = 2^2 - 3 \][/tex]
[tex]\[ f(2) = 4 - 3 \][/tex]
[tex]\[ f(2) = 1 \][/tex]
Next, apply the result to [tex]\( g \)[/tex]:
[tex]\[ g(f(2)) = g(1) \][/tex]
[tex]\[ g(1) = 1 + 1 \][/tex]
[tex]\[ g(1) = 2 \][/tex]
Thus, for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 1 \][/tex]
[tex]\[ g(f(2)) = 2 \][/tex]
So, the result is:
[tex]\[ (1, 2) \][/tex]
Therefore, the composite function [tex]\( g \cdot f \)[/tex] is correctly [tex]\( x^2 - 2 \)[/tex].
Given:
[tex]\[ f(x) = x^2 - 3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
First, we need to find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x^2 - 3 \][/tex]
Next, we apply the function [tex]\( g \)[/tex] to the result of [tex]\( f(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x^2 - 3) \][/tex]
Since the function [tex]\( g \)[/tex] is defined as [tex]\( g(x) = x + 1 \)[/tex], we substitute [tex]\( x^2 - 3 \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(x^2 - 3) = (x^2 - 3) + 1 \][/tex]
Simplifying the expression, we get:
[tex]\[ g(x^2 - 3) = x^2 - 3 + 1 \][/tex]
[tex]\[ g(x^2 - 3) = x^2 - 2 \][/tex]
Hence, the composite function [tex]\( g \cdot f \)[/tex] is:
[tex]\[ g(f(x)) = x^2 - 2 \][/tex]
Let's verify this composite function with an example input, [tex]\( x = 2 \)[/tex]:
First, calculate [tex]\( f(2) \)[/tex]:
[tex]\[ f(2) = 2^2 - 3 \][/tex]
[tex]\[ f(2) = 4 - 3 \][/tex]
[tex]\[ f(2) = 1 \][/tex]
Next, apply the result to [tex]\( g \)[/tex]:
[tex]\[ g(f(2)) = g(1) \][/tex]
[tex]\[ g(1) = 1 + 1 \][/tex]
[tex]\[ g(1) = 2 \][/tex]
Thus, for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 1 \][/tex]
[tex]\[ g(f(2)) = 2 \][/tex]
So, the result is:
[tex]\[ (1, 2) \][/tex]
Therefore, the composite function [tex]\( g \cdot f \)[/tex] is correctly [tex]\( x^2 - 2 \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.